2017
DOI: 10.1177/0013124517747032
|View full text |Cite
|
Sign up to set email alerts
|

Successes, Challenges, and Future Directions for an Urban Full Service Community Schools Initiative

Abstract: After receiving a multiyear federal grant, an urban school district and community agency that focused on family literacy implemented a comprehensive school reform initiative called Providence Full Service Community Schools (PFSCS). A host of community partners collaborated to develop the PFSCS model with the broad goal of strategically connecting teachers, families, afterschool programming, and community services, as a method for improving the well-being of students in participating schools and their families.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Interview methodology was employed in nine studies, three were multiple case studies, two used a mixed method, two included focus groups, and one incorporated direct field work. Stakeholders reported that the wraparound model (a) increased family support and engagement with the school (Anderson et al, 2017;Senior et al, 2016); (b) significantly improved school climate (Anderson et al, 2017;Anderson-Butcher et al, 2018); (c) resulted in more school-community partnerships (Anderson et al, 2017); and (d) enabled more positive transitions from juvenile justice or hospital (Maximoff et al, 2017).…”
Section: Stakeholders' Perceptions Of Efficacymentioning
confidence: 99%
“…Interview methodology was employed in nine studies, three were multiple case studies, two used a mixed method, two included focus groups, and one incorporated direct field work. Stakeholders reported that the wraparound model (a) increased family support and engagement with the school (Anderson et al, 2017;Senior et al, 2016); (b) significantly improved school climate (Anderson et al, 2017;Anderson-Butcher et al, 2018); (c) resulted in more school-community partnerships (Anderson et al, 2017); and (d) enabled more positive transitions from juvenile justice or hospital (Maximoff et al, 2017).…”
Section: Stakeholders' Perceptions Of Efficacymentioning
confidence: 99%
“…Schools and community agencies are traditionally important members of the school‐community collaboration. However, recent studies view parents and families as equal partners in the collaboration because of their critical role in their children's education (Anderson, Chen, Min, & Watkins, 2017; Bryan & Henry, 2012; Epstein & Sheldon, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Democracy is one of the core components suggested by critical and justice theories. It can be enhanced when the collaboration involves all partners in decision‐making (Sheldon, 2007), provides open and transparent communication between partners (Anderson et al, 2017), and provide fair decision‐making processes (Weiner et al, 2002). Zyngier (2011) also found that partners' empowerment was a critical component of successfully coordinating school–community collaboration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations